Effect of Leaf Syzygium aromaticum on Lymphocytes and Macrophages Mice Balb/c - Syahran Wael; Theopilus Wilhelmus Watuguly; Didik Wahyudi (Majalah Obat Tradisional, 2018)
Syzygium aromaticum as an immunomodulator contains main active compound eugenol which is able to stimulate lymphocyte proliferation and the production of macrophages. Lymphocytes have a very important role to provide protection in the body against infection. This study aims to prove the effects of extract Syzygium aromaticum leaf against increased proliferation of lymphocytes, lymphoblast and macrophages of mice Balb/c of induced Salmonella typhimurium. The method used in this study was experimental with post test only control group. Mice Balb/c were divided into 4 groups as a control group and treatment induced of Salmonella typhimurium. The first treatment group were administrated extracts of 15mg /kgbw, the second treatment 75mg/kgbw, the third treatment of 150mg/kgbw for 12days. ANOVA test showed a significant difference in lymphocyte proliferation but not lymphoblast and macrophages.